The Search - Gray, Shelley Shepard (New York : Avon Inspire, 2012)
When detective Luke Reynolds enters a Kentucky Amish community to investigate the mysterious death of Perry Borntrager, the case becomes complicated when he falls for the woman Perry had been courting before he disappeared.
Includes discussion questions and a preview of the author's next title.
Keywords: Amish -- Fiction; Murder -- Fiction -- Investigation; Crittenden County (Ky.) -- Fiction; Christian fiction; Love stories; Mystery fiction